2021
DOI: 10.13057/biodiv/d220509
|View full text |Cite
|
Sign up to set email alerts
|

The physical and chemical characteristics of several accessions of sorghum cultivated on drylands in East Nusa Tenggara, Indonesia

Abstract: Abstract. Mukkun L, Lalel HJD, Kleden YL. 2021. The physical and chemical characteristics of several accessions of sorghum cultivated on drylands in East Nusa Tenggara, Indonesia. Biodiversitas 22: 2520-2531. Many sorghums' accessions are widely cultivated in East Nusa Tenggara (ENT) Province, but no information is available on their physical and chemical properties. This study aimed to analyze the physical and chemical properties of several sorghum accessions cultivated in the dryland of ENT province. Seven s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
5
2
Order By: Relevance
“…The high starch content in sorghum genotypes indicates that sorghum can be developed into a starch source both for consumption and as an industrial raw material. This result is lower than the results of the study conducted by Mukkun [ 24 ], who reported on different sorghum accessions, which had 99.46% starch. Sorghum starch is the most beneficial type of starch because it contains a higher proportion of resistant starch (RS) and slowly digestible starch (SDS) components.…”
Section: Resultscontrasting
confidence: 79%
See 1 more Smart Citation
“…The high starch content in sorghum genotypes indicates that sorghum can be developed into a starch source both for consumption and as an industrial raw material. This result is lower than the results of the study conducted by Mukkun [ 24 ], who reported on different sorghum accessions, which had 99.46% starch. Sorghum starch is the most beneficial type of starch because it contains a higher proportion of resistant starch (RS) and slowly digestible starch (SDS) components.…”
Section: Resultscontrasting
confidence: 79%
“…Genotype G123 had high protein content, while low protein values were recorded against genotype G126. This result is lower than the findings of Queiroz [ 6 ] (8.6%–18.9%), de Morais [ 8 ] on different sorghum varieties, which attained 17.8%, and Mukkun [ 24 ], who reported, the protein content ranged from 9.03 to 12.73%. Tannin content ranged between −0.08 and, 9105.21% with a mean of 362.05 %( Table 3 ).…”
Section: Resultscontrasting
confidence: 68%
“…According to Boudries et al (2009), the density of sorghum seeds was 692.8±0.6 g/l for whites and 736.5±0.2 g/l for pigmented sorghum. According to Mukkun et al (2021), the density value of kamba in red local sorghum is 0.60 mg/L, local black sorghum is 0.58 mg/L, local brown sorghum is 0.62 mg/L, and local sorghum white at 0.83 mg/L.…”
Section: Bulk Density True Density and Seed Porositymentioning
confidence: 99%
“…Polyphenols are a group of chemical substances found in plants. This substance has a distinctive sign that it has many phenol groups in its molecule (Mukkun et al 2021). Polyphenols are often found in polar glycosides and are readily soluble in polar solvents (Alara et al 2021).…”
Section: Total Polyphenol and Caffeine Contentmentioning
confidence: 99%